Ligand conjugated antisense oligonucleotide for the treatment of transthyretin amyloidosis: preclinical and phase 1 data. (7th December 2020) - Viney, Nicholas J.; Guo, Shuling; Tai, Li‐Jung; Baker, Brenda F.; Aghajan, Mariam; Jung, Shiangtung W.; Yu, Rosie Z.; Booten, Sheri; Murray, Heather; Machemer, Todd; Burel, Sebastien; Murray, Sue; et al.
Abstract: Aims: Amyloidogenic transthyretin (ATTR) amyloidosis is a fatal disease characterized by progressive cardiomyopathy and/or polyneuropathy. AKCEA‐TTR‐LRx (ION‐682884) is a ligand‐conjugated antisense drug designed for receptor‐mediated uptake by hepatocytes, the primary source of circulating transthyretin (TTR). Enhanced delivery of the antisense pharmacophore is expected to increase drug potency and support lower, less frequent dosing in treatment. Methods and results: AKCEA‐TTR‐LRx demonstrated an approximate 50‐fold and 30‐fold increase in potency compared with the unconjugated antisense drug, inotersen, in human hepatocyte cell culture and mice expressing a mutated human genomic TTR sequence, respectively. This increase in potency was supported by a preferential distribution of AKCEA‐TTR‐LRx to liver hepatocytes in the transgenic hTTR mouse model. A randomized, placebo‐controlled, phase 1 study was conducted to evaluate AKCEA‐TTR‐LRx in healthy volunteers (ClinicalTrials.gov: NCT03728634). Eligible participants were assigned to one of three multiple‐dose cohorts (45, 60, and 90 mg) or a single‐dose cohort (120 mg), and then randomized 10:2 (active : placebo) to receive a total of 4 SC doses (Day 1, 29, 57, and 85) in the multiple‐dose cohorts or 1 SC dose in the single‐dose cohort. The primary endpoint was safety and tolerability; pharmacokinetics and pharmacodynamics were secondary endpoints. All randomized participants completed treatment. No serious adverse events were reported. In the multiple‐dose cohorts, AKCEA‐TTR‐LRx reduced TTR levels from baseline to 2 weeks after the last dose of 45, 60, or 90 mg by a mean (SD) of −85.7% (8.0), −90.5% (7.4), and −93.8% (3.4), compared with −5.9% (14.0) for pooled placebo ( P < 0.001). A maximum mean (SD) reduction in TTR levels of −86.3% (6.5) from baseline was achieved after a single dose of 120 mg AKCEA‐TTR‐LRx . Conclusions: These findings suggest an improved safety and tolerability profile with the increase in potency achieved by productive receptor‐mediated uptake of AKCEA‐TTR‐LRx by hepatocytes and supports further development of AKCEA‐TTR‐LRx for the treatment of ATTR polyneuropathy and cardiomyopathy.